PENGARUH PEMBERIAN SEDIAAN SERBUK KERING JAHE MERAH (Zingiber officinale var. rubrum) TERHADAP KOLESTEROL TOTAL - Oktoviani ., (Jurnal Kesehatan Medika Saintika, 2020)
Red ginger ( Zingiber officinale) as traditional medicine is assumed affecting the lipid profile of patients with dyslipidemia. Dyslipidemia is a risk factor of several degenerative diseases. The research is a clinical trial in eligible 33 patients. The Inclusion criteria were dyslipidemia with diabetes mellitus patients in age range 30-60 years. The Exclusion criteria were the presence of gastric irritation, hypothyroidism, impaired of liver function; kidney; and heart, pregnant woman and breast feeding mother. The treatment group received 3 grams dried red ginger powder per day for 30 days without standard drug therapy. The control group was not given any treatment. Both groups examined on the total cholesterol levels before and after the study. Changes in the total cholesterol levels before and after study were tested by independent sample test with a significance value of p <0.05. The research concluded that the dried red ginger powder significantly affect total cholesterol (p = 0.000) that was shown by average difference value was 57.489 mg/ dL.